RETRACTED: Correlation Analysis Between Required Surgical Indexes and Complications in Patients With Coronary Heart Disease - Tao, Meiyi; Yao, Xiaoling; Sun, Shengli; Qin, Yuelan; Li, Dandan; Wu, Juan; Xiong, Yican; Teng, Zhiyu; Zeng, Yunfei; Luo, Zuoheng (Frontiers in Surgery, 2022)
215 patients with coronary heart disease were analyzed with SPSS. Samples of different genders showed significance in the obtuse marginal branch of left circumflex branch×1, the diagonal branch D1×1, and the ms PV representation. Patients with left circumflex branch occlusion are more male and tend to be younger. Age displayed a positive correlation with left IMT and right IMT respectively. This indicates that as the age increases, the values of left intima-media thickness IMT and right intima-media thickness become higher. Samples of different CHD types showed significance in the obtuse marginal branch of the left circumflex branch×1, the middle part of RCA×1, and the middle part of the left anterior descending branch×1.5. For non-ST-segment elevation angina pectoris with acute total vascular occlusion, the left circumflex artery is the most common, followed by the right coronary artery and anterior descending branch. Ultrasound of carotid intima-media thickness in patients with coronary heart disease can predict changes in left ventricular function, but no specific correlation between left and right common carotid intima-media thickness was found. Samples with or without medical history of ASCVD showed significance in the branch number of coronary vessel lesions. The value of the branch number of coronary vessel lesions in patients with atherosclerotic cardiovascular disease is higher than in those without atherosclerotic cardiovascular disease. Whether there is any complication is significant with the distance of left circumflex branch×1, the middle segment of left anterior descending branch×1.5, and the distance of left anterior descending branch×1. For patients without complications, the values in the distal left circumflex branch×1, the middle left anterior descending branch×1.5, and the distal left anterior descending branch×1 were higher than those in patients with complications. The VTE scores respectively showed a positive correlation with the proximal part of RCA×1, branch number of coronary vessel lesions, posterior descending branch of left circumflex branch×1, distal part of left circumflex branch×1, and the middle part of left anterior descending branch×1.5.